Cyber-harassment victimization in Portugal: Prevalence, fear and help-seeking among adolescents - Pereira, Filipa (2016)
Cyber-harassment is one of today's problems in adolescent health. This study aimed to determine the prevalence of cyber-victimization among Portuguese adolescents. It also explored its nature, patterns and victim's reactions of fear and help-seeking. A representative sample of 627 adolescents, aged 12-16, enrolled in schools from northern Portugal and Azores answered an online survey. Cyber-victimization was widely experienced by these adolescents, mainly among older adolescents. Results evidenced a high prevalence rate of adolescents (66.1%) double involved as both cyber-victim and cyber-aggressor. Although. not all adolescents reported fear (37%) or sought help (45.9%), persistent victimization increased fear: In turn, fear increased help-seeking behaviors. Cyber-victims were more afraid encountering unknown cyber-aggressors (vs. acquainted) and when victimized by older males (vs. younger females cyber-aggressors). Younger girls reported more fear and more help-seeking behaviors while older boys were more often victim-aggressors. The subgroup of victim-aggressors was both the target of a higher diversity of cyber-victimization behaviors than the victim-only subgroup and also engaged in fewer help-seeking behaviors. Those adolescents who sought help considered it helpful. Implications for educational, social and political practices are discussed. (c) 2016 Elsevier Ltd. All rights reserved.